Cnc Machine Design (Computer Numeric Control) Mini Plotter For Arduino Based Souvenir Craft - Sindhu Rakasiwi; Haryo Kusumo (Universitas PGRI Semarang, 2022)
The plotter is a graphic printer that draws using ink pens, the plotter is also the first output device capable of printing large-sized images of architectural and engineering drawings. A plotter is a type of printer that is specifically designed to produce computer output in the form of images or graphics. There are many types of plotters, one of which is the pen plotter, which has one or more colored pens for drawing on transparent paper or plastic and producing a line output. CNC (Computer Numerical Controller) is one of the machine control tools in large industrial factories. With the CNC can control most of the tools one example is as a controller of a 2-dimensional plotter. This research designs a 2-dimensional plotter using Arduino UNO-based CNC. This 2-dimensional plotter has an accuracy of 97.947% and a precision of 99.985%. This 2-dimensional plotter is capable of operating up to a distance of 4cm with a resolution of 0.01cm.